The contribution of information systems to increase tax revenues: An applied research at the General Commission of Taxes (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to study the contribution of tax information systems to increase tax revenues, and to identify how efficiently used information systems currently by the tax authority and their effectiveness in the detection of irregularities by the tax payers such as the cleclaration of incorrect statements that do not show real results of their business activities or hide information from sources related to their income subject to tax, which would negatively affect the outcome of tax revenues and thus damage important sourse of the public treasury of the states resources. The data of research was collected by studying and analysing the tax information systems used by the General Commission of taxs and its branches and a number of practical case studies drawn from the records of the mentioned commission. The research found a number of results the most important is the existence of a clear effect of tax information systems in increacing tax revenues effect Also, the tax information systems used by the tax authority were not efficient and effective to enabling its staff to determine the incomes of tax payers accurately and objectively and facilitating the process of settling tax accounts.